Partial Discharge Classification With 1D Convolutional Neural Network - Thepjit Cheypoca; Wiboon Promphanich; Aung Ye Thway; Angelina Phimpissada Hankae; Siwakorn Jeenmuang; Norasage Pattanadech (My University, 2024)
This paper introduces a novel approach for classifying with the 1D Convolutional Neural Network model for partial discharge patterns, that consists of corona discharge, surface discharge and internal discharge. The PD measuring circuit suggested in IEC 60270:2000 is used to record Partial discharge signals. Independent parameters such as phase and charge of PD patterns were recorded. The Artificial Neural Network for the classification model was constructed. Moreover, 2×1D CNN feature extraction was utilized to reduce the curse of dimensionality in the dense layer of the proposed PD classification model. 80% of the recorded data will be used as a training data and 20% recorded data was used for testing of the classification models. Impacts of neuron numbers and network architecture on the PD classification performance will be observed.
Keywords: High voltage insulation and dielectric phenomena; Water Quality Monitoring Technologies; Advanced Sensor and Control Systems